2021
DOI: 10.5194/esd-2021-100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic regimes of the Greenland Ice Sheet emerging from interacting melt-elevation and glacial isostatic adjustment feedbacks

Abstract: Abstract. The stability of the Greenland Ice Sheet under global warming is governed by a number of dynamic processes and interacting feedback mechanisms in the ice sheet, atmosphere and solid Earth. Here we study the long-term effects due to the interplay of the competing melt-elevation and glacial isostatic adjustment (GIA) feedbacks for different temperature step forcing experiments with a coupled ice-sheet and solid-Earth model. Our model results show that for warming levels above 2 °C, Greenland could beco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…When ice melts, the surface elevation decreases and the ice is subjected to warmer temperatures and larger melt rates, leading to further ice melt, and potential ice sheet destabilization (Levermann et al., 2013). However, GIA counteracts this feedback by increasing the surface elevation when ice melts (Zeitz et al., 2022), and fast uplift above LV regions can amplify this feedback. For marine terminating glaciers, GIA can stabilize the grounding line.…”
Section: Discussionmentioning
confidence: 99%
“…When ice melts, the surface elevation decreases and the ice is subjected to warmer temperatures and larger melt rates, leading to further ice melt, and potential ice sheet destabilization (Levermann et al., 2013). However, GIA counteracts this feedback by increasing the surface elevation when ice melts (Zeitz et al., 2022), and fast uplift above LV regions can amplify this feedback. For marine terminating glaciers, GIA can stabilize the grounding line.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that, to some extent, the glacial isostatic adjustment can counteract the positive feedbacks that are believed to cause a hysteresis of the Greenland ice sheet with global warming [21]. While the uplifting of the bedrock due to decreasing ice load with increasing temperatures slows down the ice loss, a regrowth of the ice sheet is only facilitated when the temperature decreases again.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time scale of this feedback is still debated [22,23] and is often neglected on sub-millennial time scales [7]. The simulated oscillations of the ice sheet on a decamillennial time scale are believed to be the consequence of an interplay between bedrock uplift and melt-elevation feedback in PISM [21]. We find that the intermediate states are at least partially caused by the interplay between the isostatic glacial adjustment and melt-elevation feedback and we find fewer intermediate states without bedrock uplifting (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is also underlined by our control run experiments which show convergence of their ice volume towards steady states rather than large scale cyclic behaviour. Other feedbacks and processes than MISI might influence the stability regime of grounding lines, e.g., bedrock uplift and the melt-elevation feedback can lead to cyclic behaviour (Zeitz et al, 2021). We here exclude those feedbacks and only focus on MISI.…”
Section: Potential States Of Antarctic Grounding Linesmentioning
confidence: 99%